Molecular structure of promoter-bound yeast TFIID - Olga Kolesnikova (Nature Portfolio, 2018)
Transcription preinitiation complex assembly begins with the recognition of the gene promoter by the TATA-box Binding Protein-containing TFIID complex. Here the authors present a Cryo-EM structure of promoter-bound yeast TFIID complex, providing a detailed view of its subunit organization and promoter DNA contacts.